Modelling the Behaviour of Millennials towards the Adoption of Mobile E-Money Services in National Capital Region of the Philippines using Structural Equation Modelling - Lovely Aducal (HM Journals, 2024)
This study investigates the behavioural intention of millennials towards the adoption of mobile e-money services. The Theory of Planned Behaviour as the theoretical foundation with Attitude, Subjective Norms, and Perceived Behavioural Control variables and Structural Equation Modelling as the modelling technique were employed to identify what factor(s) influence the millennial’s behavioural intent. A combined online and paper-and-pencil survey form was employed to assess how electronic banking through the use of mobile e-wallets is perceived by the millennials residing in the National Capital Region of the Philippines. The sociodemographic profile of the respondents and their banking experiences, including their access to financial products and services, are other goals of this study. The research concludes that millennials’ attitude and perceived behavioural control have a significant impact on their intent to adopt mobile e-money services, and the majority have access to financial products and services. The millennials’ subjective norms have a positive effect, but it is not significant. Additionally, the respondents’ gender and whether they own a bank account or not were used for moderation analysis. The research findings showed that both variables do not have a significant effect on the links between variables. Results of this research could guide the financial regulatory bodies in their policy-making activities, the users of electronic financial products in their financial endeavours, and the government, ultimately, to achieve its financial goals.